1999
DOI: 10.1143/jjap.38.l961
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Optical Stop Band and Reflection Peak in Synthetic Opal Infiltrated with Liquid Crystal and Conducting Polymer as Photonic Crystal

Abstract: The optical stop band in the transmission spectra and the peak in the reflection spectra of opals with a three-dimensional periodic structure shift drastically upon infiltration with organic materials such as liquids, liquid crystals and conducting polymers. In these infiltrated opals, the stop band and reflection peak have been confirmed to be tunable by adjusting various conditions such as temperature and applied voltage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 6 publications
0
55
0
Order By: Relevance
“…Band tuning in three-dimensional photonic crystals via the ambient temperature was first demonstrated in liquid crystal materials [62,77,78]. Large band shifts were also shown in opals filled with a suitable material exhibiting a phase transition in a convenient temperature range.…”
Section: Tunable Photonic Crystalsmentioning
confidence: 96%
See 1 more Smart Citation
“…Band tuning in three-dimensional photonic crystals via the ambient temperature was first demonstrated in liquid crystal materials [62,77,78]. Large band shifts were also shown in opals filled with a suitable material exhibiting a phase transition in a convenient temperature range.…”
Section: Tunable Photonic Crystalsmentioning
confidence: 96%
“…The spectral width of the PSB is dependent on refractive index contrast and can be changed by filling the voids of opal with suitable substances [60]. Modern technology allows to fill opal voids with various dielectrics [61], semiconductors [38,60], liquid crystals [62], and metals [63]. As an example, Fig.…”
Section: Artificial Opalsmentioning
confidence: 99%
“…[172] Conducting polymers have a great interest and can be synthesized in the preformed opals by electro- [173] or other polymerization, and can show electrical conductivity and luminescent properties. [174] If the eletropolymerization is performed on a thick sedimented opal, the thickness of the final infiltrated opal can be controlled by the reaction time.…”
Section: Infiltrated Opalsmentioning
confidence: 99%
“…It has been demonstrated that anions in an electrolyte can be electrochemically doped into conducting polymers such as polyaniline and polythiophene, which can cause a change in the refractive index of the polymer. [12,13] As a result, the optical stopband of silica opals can be finely tuned by electrochemical doping of anions into the conducting polymer matrix infiltrated into the opals. [12] In the present paper, we employ an elegant nanochemical technique to demonstrate the fabrication of polyaniline (PANI), a conducting polymer, inverse opals by templating ordered colloidal assemblies.…”
mentioning
confidence: 99%